2021
DOI: 10.1186/s12909-021-02572-4
|View full text |Cite
|
Sign up to set email alerts
|

Moral judgement development during medical student clinical training

Abstract: Background Whereas experience and cognitive maturity drives moral judgement development in most young adults, medical students show slowing, regression, or segmentation in moral development during their clinical years of training. The aim of this study was to explore the moral development of medical students during clinical training. Methods A cross-sectional sample of medical students from three clinical years of training were interviewed in group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
2
0
3
Order By: Relevance
“…Fourthly, “insensitivity” to difficult ethical (or other non-medical) aspects of healthcare practice can be acquired in the process of informal and tacit modes of secondary socialization (so called “hidden curriculum”) by which professional cultures are communicated to new members, i.e., medical students and young physicians (Hafferty & Franks, 1994 ; Vaidyanathan 2015 ). When senior physicians, i.e., the main agents of the professional socialization, act paternalistically towards their patients, stick to the rigid hierarchical authority structure of the medical teamwork and healthcare decision-making, and when they present themselves as being desensitized and morally detached, there is a high risk that their younger colleagues will mimic these emotional and behavioral patterns in their future professional life (Lind, 2000 ; Hren et al, 2011 ; McDonald et al, 2021 ). The revealed reduction in frequency of ethical (and other non-medical) problems encountered by Polish physicians, when considering their years of experience, provides support for this explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, “insensitivity” to difficult ethical (or other non-medical) aspects of healthcare practice can be acquired in the process of informal and tacit modes of secondary socialization (so called “hidden curriculum”) by which professional cultures are communicated to new members, i.e., medical students and young physicians (Hafferty & Franks, 1994 ; Vaidyanathan 2015 ). When senior physicians, i.e., the main agents of the professional socialization, act paternalistically towards their patients, stick to the rigid hierarchical authority structure of the medical teamwork and healthcare decision-making, and when they present themselves as being desensitized and morally detached, there is a high risk that their younger colleagues will mimic these emotional and behavioral patterns in their future professional life (Lind, 2000 ; Hren et al, 2011 ; McDonald et al, 2021 ). The revealed reduction in frequency of ethical (and other non-medical) problems encountered by Polish physicians, when considering their years of experience, provides support for this explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Somit scheint wie bereits in vorangegangenen Studien berichtet die moralische Kompetenz in höheren Studiensemestern eher zu stagnieren bzw. sogar abzunehmen 1 3 4 28 . Weder die größere praktische Erfahrung der Studierenden in höheren Fachsemestern noch die erfolgte Teilnahme am Studienfach Ethik scheinen sich daher auf die moralische Kompetenz der Studierenden positiv auszuwirken 29 .…”
Section: Diskussionunclassified
“…Wären diese Studierenden hypothetisch eingeschlossen worden, wäre mit einer Verfälschung der Ergebnisse zu rechnen gewesen, da beide Aspekte sich eigenständig auf die moralische Kompetenz auswirken können 25 26 27 . Zudem muss Erwähnung finden, dass die erreichten C-Werte der Studierenden insgesamt deutlich unter den zu erwartenden Werten im Vergleich zu Vorstudien lagen 1 4 28 . Möglicherweise ist dies mit der relativ geringen Teilnehmendenzahl und dem damit verbundenen Stichprobencharakter zu erklären.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Research suggested the distress resulting from professionalism dilemmas induced long-lasting emotional episodes compromising mental well-being. Medical students felt burnout [ 14 ], emotional breakdown [ 15 , 16 ], and guilty [ 5 , 17 ] in the face of professionalism dilemmas. Some students have even dropped out of medical school or chosen a non-clinical specialty as a result [ 18 ].…”
Section: Introductionmentioning
confidence: 99%